Allogenic Fc Domain-Facilitated Uptake of IgG in Nasal Lamina Propria: Friend or Foe for Intranasal CNS Delivery? - Simone Ladel; Johannes Flamm; Arghavan Soleimani Zadeh; Dorothea Filzwieser; Julia-Christina Walter; Patrick Schlossbauer; Ralf Kinscherf; Katharina Lischka; Harald Luksch; Katharina Schindowski (MDPI AG, 2018)
Background: The use of therapeutic antibodies for the treatment of neurological diseases is of increasing interest. Nose-to-brain drug delivery is one strategy to bypass the blood brain barrier. The neonatal Fc receptor (FcRn) plays an important role in transepithelial transcytosis of immunoglobulin G (IgG). Recently, the presence of the FcRn was observed in nasal respiratory mucosa. The aim of the present study was to determine the presence of functional FcRn in olfactory mucosa and to evaluate its role in drug delivery. Methods: Immunoreactivity and messenger RNA (mRNA) expression of FcRn was determined in ex vivo porcine olfactory mucosa. Uptake of IgG was performed in a side-by-side cell and analysed by immunofluorescence. Results: FcRn was found in epithelial and basal cells of the olfactory epithelium as well as in glands, cavernous bodies and blood vessels. Allogenic porcine IgGs were found time-dependently in the lamina propria and along axonal bundles, while only small amounts of xenogenic human IgGs were detected. Interestingly, lymphoid follicles were spared from allogenic IgGs. Conclusion: Fc-mediated transport of IgG across the nasal epithelial barrier may have significant potential for intranasal delivery, but the relevance of immune interaction in lymphoid follicles must be clarified to avoid immunogenicity.